Factors that influence employees job satisfaction - Othman, Manisah; Kamarohim, Norazlina; Loke, Kaar Maan (Future Academy, 2018)
The satisfaction brings implication to lives. There is one-third to one-half of people spend their life on work. On the assumption that people are happy with their job and have the passion for it, their lives then become much enjoyable. This research aimed to evaluate the comprehensive job satisfaction level of Asia Brands Berhad, thus reveal the factors that commit to job satisfaction in the organization. The outcome of the research is mainly to aid the organization to enhance job satisfaction and motivation of employees efficiently. The objectives of this study were to determine whether benefits, work environment and rewards are related to the employee’s satisfaction. Employees from Asia Brands Berhad were randomly selected as research participants. Total 180 questionnaires administered, 150 were completed and returned and 136 were found useful. Finding from this study, it can be seen that the factor that influence employees job satisfaction in Asia Brands Berhad such as benefit/compensation, work environment and supervisor support are having positive relationship.